Physiologic selectivity of inseticides to wasps predators of the coffee leafminer - Gusmão, Marcos Rafael; Picanço, Marcelo; Gonring, Alfredo Henrique Rocha; Moura, Marcelo Fialho (Pesquisa Agropecuaria Brasileira, 2000)
The selectivity of the insecticides chlorpyrifos, deltamethrin, dimethoate, ethion, monocrothophos and permethrin to the predatory wasps Apoica pallens Fab., Brachygastra lecheguana Latreille and Polistes versicolor versicolor Olivier (Hymenoptera: Vespidae) was studied, in laboratory, using 50% and 100% of the dosages used for controlling the coffee leafminer, Perileucoptera coffeella Guérin-Meneville (Lepidoptera: Lyonetiidae). Deltamethrin was selective in favour of P. versicolor versicolor and A. pallens. Ethion showed median selectivity in favour of P. versicolor versicolor and A. pallens and good selectivity to B. lecheguana. The other insecticides were not selective in favour of the predatory wasps. The order of tolerance to deltamethrin was: P. versicolor versicolor > A. pallens > B. lecheguana. To ethion, the order was: B. lecheguana > P. versicolor versicolor > A. pallens. Chlorpyrifos, deltamethrin, dimethoate, monocrothophos and permethrin presented similar toxicity to the wasps in both dosages used. On the other hand ethion reduced its impact on A. pallens and P. versicolor versicolor when applied in subdosages.